The costs of traditional construction methods against modular construction methods in South Africa: the perception of construction professionals - de Jager, Ashley Mirlné (Department of Construction Economics and Management, 2026)
This study aims to gain insight into how construction professionals in South Africa perceive the cost of construction with regards to modular construction methods versus traditional construction methods. This study aims to compare the benefits and drawbacks of modular construction versus traditional construction methods. Modular construction involves building certain elements of the structure in a factory setting before transporting them to the construction site for assembly, while traditional construction involves building all the elements of a structure on-site. The research focuses on factors such as cost, time efficiency, quality control, and environmental impact. The study finds that construction professionals perceive modular construction leads to cost savings and improved quality control more than that of traditional construction projects. Overall, the choice between modular and traditional construction should be based on the specific needs and goals of the project and the client's specifications as per contract data. The findings of this study revealed that modular construction is perceived to be more affordable and faster to complete than traditional construction methods. The cost and duration of different stages during construction are the main factors that create cost variances. More construction professionals have experience with traditional construction projects in comparison to modular construction projects. However, modular construction produces less waste, is considered safer, and uses less labour during the construction process. Based on the findings in the study, it can be concluded that modular construction is a cost-effective and efficient method of construction that can save time and money compared to traditional construction methods. However, it is important to note that certain factors can create cost variances between the two methods, such as the cost and duration of different stages during construction. These factors are directly connected to the cost and time spent within the various stages of construction. The findings from the study revealed that during the various stages of construction; site preparation, foundations and excavations, ground floor construction, superstructure work, roof construction, external and internal finishes, and site handover, it was found that construction professionals perceive traditional construction methods to be more costly and take more time to complete in comparison to modular construction methods. Overall, the choice of construction method should be based on the specific needs and goals of the project, as well as the trade-offs between cost, time efficiency, quality, safety, and environmental impact. To gather data for this study, 91 participants participated and complete an online survey. Google Forms, a widely recognized web-based survey platform, was employed to administer the questionnaire. The survey itself consisted of a series of questions designed to assess participants' understanding and attitudes towards the topic of interest. Upon completion, the collected responses were automatically stored in a centralized database for further analysis. To analyse the collected data, the mean item score method was employed. This approach involves calculating the average score for each survey item, providing a comprehensive overview of participants' responses. The study employed a positivist philosophy, adhering to the belief that knowledge can be derived from objective observation and measurement. To achieve this, the research adopted a deductive approach, whereby hypotheses were formulated based on existing theories and then tested using empirical data. A mono-method approach was implemented, relying solely on quantitative data collection and analysis. This quantitative approach involved collecting numerical data and analysing it using statistical methods. The study was limited to a specific time horizon, providing a record of the hypothesis under investigation